Kajian Aset Komunitas dalam Menelaah Kendala Implementasi Kebijakan Penanganan Konflik Sosial Perkelahian Massal ‘Tawuran’ di Kota Jakarta Pusat - Muhammad Ajie Tori Faizal; Isbandi Rukminto Adi (VISA: Journal of Vision and Ideas, 2024)
Based on Podes BPS RI data collection, Central Jakarta City is the city with the highest number of incidents and the ratio of sub-districts that have experienced mass brawls. Based on the description above, it is certainly interesting that the City of Central Jakarta, which contains many government agencies (where of course many policies are formulated), educational facilities and even office complexes as business centers, actually has widespread social conflict, mass chaos, especially brawls within it. Moving on from these conditions, this research aims to overcome the obstacles that occur in the implementation of policies for handling social conflict in the Central Jakarta City area through the lens of community assets to be able to describe not only the situation of policy makers but also the condition of the social welfare of the community. The research method used is a qualitative descriptive method, information obtained through interviews, observation and documentation studies. The research results show that there are obstacles both in terms of target community factors which include predisposition, behavioral, financial, social-spiritual, physical-environmental elements, even elements of digital capital from teenagers, families and the environment. And in terms of reinforcing factors (officers) include elements of predisposition, work behavior, and resources from officers and related institutions. And finally, in terms of the 'brawl' mass conflict resolution program itself. The various obstacles from various factors then show that there is a need to revitalize policy implementation that is more holistic across sectors covering all aspects of both the target community and policy implementing institutions so that the implementation of policies for handling social conflict can also increase the level of social welfare of the wider community.Based on Podes BPS RI data collection, Central Jakarta City is the city with the highest number of incidents and the ratio of sub-districts that have experienced mass brawls. Based on the description above, it is certainly interesting that the City of Central Jakarta, which contains many government agencies (where of course many policies are formulated), educational facilities and even office complexes as business centers, actually has widespread social conflict, mass chaos, especially brawls within it. Moving on from these conditions, this research aims to overcome the obstacles that occur in the implementation of policies for handling social conflict in the Central Jakarta City area through the lens of community assets to be able to describe not only the situation of policy makers but also the condition of the social welfare of the community. The research method used is a qualitative descriptive method, information obtained through interviews, observation and documentation studies. The research results show that there are obstacles both in terms of target community factors which include predisposition, behavioral, financial, social-spiritual, physical-environmental elements, even elements of digital capital from teenagers, families and the environment. And in terms of reinforcing factors (officers) include elements of predisposition, work behavior, and resources from officers and related institutions. And finally, in terms of the 'brawl' mass conflict resolution program itself. The various obstacles from various factors then show that there is a need to revitalize policy implementation that is more holistic across sectors covering all aspects of both the target community and policy implementing institutions so that the implementation of policies for handling social conflict can also increase the level of social welfare of the wider community.